An Alternative Design Topology for Metropolitan Area Networks - Antonius Suhartomo (LPPM ITB, 2012)
One of the key issues in designing a network topology is vulnerability. The vulnerability parameter measures the resistance of a network to disruption of operation after the failure of certain stations or communication links. One counter-measure to address the vulnerability of a network is edge connectivity.In this paper, a more selective concept of edge connectivity is introduced, called component order edge connectivity for MAN topology design. This parameter equals the smallest number of edges that must be removed in order to ensure that the order of each component of the resulting sub -network or sub-graph is less than k.